Identity, narcissism and suicide attempt in the elderly - Matusevich, León Daniel; Vega, Ana Laura; Donadio, Paula Daniela (Revista del Hospital Italiano de Buenos Aires, 2018)
During the aging process several changes occur that may surprise unfavorably those who are more fragile. One of the most significant challenges that occur in the elderly is related with the lost of the previous identity which can lead to unforeseeable consequences, where the suicide attempt may seem to be the last and the most desperate way to regain control. Old age involves various changes and losses which will be experienced differently by every person according to their one personality and life story. To be able to fully comprehend this process will allow us to understand this stage of life in each singularity. In this article we will analyze three life stories illustrating people who lost the meaning of what defined them as human beings